2014
DOI: 10.1128/jb.02017-14
|View full text |Cite
|
Sign up to set email alerts
|

Two Fis Regulators Directly Repress the Expression of Numerous Effector-Encoding Genes in Legionella pneumophila

Abstract: Legionella pneumophila is an intracellular human pathogen that utilizes the Icm/Dot type IVB secretion system to translocate a large repertoire of effectors into host cells. For most of these effectors, there is no information regarding their regulation. Therefore, the aim of this study was to examine the involvement of the three L. pneumophila Fis homologs in the regulation of effector-encoding genes. Deletion mutants constructed in the genes encoding the three Fis regulators revealed that Fis1 (lpg0542 gene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 64 publications
(86 reference statements)
2
19
0
Order By: Relevance
“…S1 and S2), we were interested in examining whether this island is silenced by NAPs. The H-NS NAP is not present in Legionella, but three Fis paralogs (Fis1, Fis2, and Fis3), which are also NAPs, were previously shown to directly repress the expression of EEGs (32). Examination of the lciRS-lciE intergenic region led to the identification of four potential Fis regulatory elements (TG-N 13 -C), two close to or overlapping the Ϫ10 promoter element of lciE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 and S2), we were interested in examining whether this island is silenced by NAPs. The H-NS NAP is not present in Legionella, but three Fis paralogs (Fis1, Fis2, and Fis3), which are also NAPs, were previously shown to directly repress the expression of EEGs (32). Examination of the lciRS-lciE intergenic region led to the identification of four potential Fis regulatory elements (TG-N 13 -C), two close to or overlapping the Ϫ10 promoter element of lciE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glycerol was added to a concentration of 50%, and the purified protein was then stored at -20°C. A gel mobility shift assay was performed as previously described (32), with a few modifications. The regulatory region lciE (176 bp) was amplified by PCR using the primers listed in Data Set S1 and 3= end labeled with digoxigenin (DIG) by using DIG-11-ddUTP (Roche).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…An additional type of interplay between regulators is the direct regulation of a single effector by multiple regulators. Several such combinations were thus far described for effector‐encoding genes regulated by CpxR: (i) A single effector (Ceg33) was shown to be activated by both CpxR and PmrA (Altman and Segal, ); (ii) Four effectors (CegC2, Ceg7, Ceg18 and Ceg29) were shown to be activated by PmrA and repressed by CpxR ([Altman and Segal, ] and this study); (iii) Three effectors (CegC1, MavT and Lpg2461) were shown to be repressed at the level of transcription by CpxR and at the level of translation by CsrA ([Rasis and Segal, ] and this study); and (iv) Two effectors (SidM/DrrA and CegC4) were shown to be repressed by both CpxR and the Fis regulators (Altman and Segal, ; Zusman et al ., ). Interestingly, there are combinations of dual direct regulation that were not observed: regulation by both PmrA and CsrA, as well as activation by CpxR and repression by CsrA.…”
Section: Discussionmentioning
confidence: 97%
“…We propose that binding of the cis -encoded Anti-hfq sRNA to hfq mRNA in exponential growth leads to low translation of Hfq, whereas when the expression of Anti-hfq sRNA decreases in the transmissive phase, high expression of Hfq is possible. This leads to the expression of several Dot/Icm secreted substrates, global regulators like Fis1 and Fis2 that are implicated in the regulation of virulence traits (44) and probably of several of the many growth phase dependently regulated sRNAs that we identified earlier (13) (Fig. 8).…”
Section: Discussionmentioning
confidence: 92%